Case series of infective endocarditis caused by Granulicatella species. (February 2015) - Adam, Eduardo Leal; Siciliano, Rinaldo Focaccia; Gualandro, Danielle Menosi; Calderaro, Daniela; Issa, Victor Sarli; Rossi, Flavia; Caramelli, Bruno; Mansur, Alfredo Jose; Strabelli, Tania Mara Varejao
Highlights: We report four cases of infective endocarditis caused by Granulicatella species. Subacute symptoms and large vegetations are frequently observed. The development of heart failure, embolism and perivalvular abscess is common. Summary: Background: Nutritionally variant streptococci (NVS) are Gram-positive cocci characterized by their dependence on pyridoxal or cysteine supplementation for growth in standard blood culture media. They are responsible for severe infections in immunocompetent and immunosuppressed hosts, including infective endocarditis (IE). NVS have been divided into two different genera, Granulicatella and Abiotrophia . Methods: We report four cases of IE caused by Granulicatella species, including clinical presentation, echocardiographic characteristics, treatments received, and outcomes. We also performed a literature search for previously reported cases of IE caused by Granulicatella species to better characterize this condition. Results: A total of 29 cases of Granulicatella endocarditis were analyzed, including the four newly reported cases. The aortic (44%) and mitral (38%) valves were those most commonly affected. Multivalvular involvement was observed in 13% of cases. The mean vegetation length was 16 mm. Complications were frequent, including heart failure (30%), embolism (30%), and perivalvular abscess (11%). The most frequent antibiotic regimen (85%) was penicillin or one of its derivatives plus gentamicin. The mortality rate was 17%. Conclusions: Endocarditis due to Granulicatella species is a rare and severe condition. Complications are frequent despite the use of appropriate antibiotic regimens.